A Local Region Molecular Dynamics Simulation Method for Nanoscale Sliding Contacts - Rui-Ting Tong; Geng Liu; Tian-Xiang Liu (Chinese Journal of Mechanical Engineering, 2018)
Abstract Computational efficiency and accuracy always conflict with each other in molecular dynamics (MD) simulations. How to enhance the computational efficiency and keep accuracy at the same time is concerned by each corresponding researcher. However, most of the current studies focus on MD algorithms, and if the scale of MD model could be reduced, the algorithms would be more meaningful. A local region molecular dynamics (LRMD) simulation method which can meet these two factors concurrently in nanoscale sliding contacts is developed in this paper. Full MD simulation is used to simulate indentation process before sliding. A criterion called contribution of displacement is presented, which is used to determine the effective local region in the MD model after indentation. By using the local region, nanoscale sliding contact between a rigid cylindrical tip and an elastic substrate is investigated. Two two-dimensional MD models are presented, and the friction forces from LRMD simulations agree well with that from full MD simulations, which testifies the effectiveness of the LRMD simulation method for two-dimensional cases. A three-dimensional MD model for sliding contacts is developed then to show the validity of the LRMD simulation method further. Finally, a discussion is carried out by the principles of tribology. In the discussion, two two-dimensional full MD models are used to simulate the nanoscale sliding contact problems. The results indicate that original smaller model will induce higher equivalent scratching depth, and then results in higher friction forces, which will help to explain the mechanism how the LRMD simulation method works. This method can be used to reduce the scale of MD model in large scale simulations, and it will enhance the computational efficiency without losing accuracy during the simulation of nanoscale sliding contacts.